Inhibiting the inflammasome with MCC950 counteracts muscle pyroptosis and improves Duchenne muscular dystrophy - Dubuisson, Nicolas; Davis-López de Carrizosa, María A.; Versele, Romain; Selvais, Camille M.; Noel, Laurence; Van den Bergh, P. Y. D.; Brichard, Sonia M.; Abou-Samra, Michel (Frontiers in Immunology, 2022)
Background Duchenne muscular dystrophy (DMD) is the most common inherited human myopathy. Typically, the secondary process involving severe inflammation and necrosis exacerbate disease progression. Previously, we reported that the NLRP3 inflammasome complex plays a crucial role in this disorder. Moreover, pyroptosis, a form of programmed necrotic cell death, is triggered by NLRP3 via gasdermin D (GSDMD). So far, pyroptosis has never been described either in healthy muscle or in dystrophic muscle. The aim of this study was to unravel the role of NLRP3 inflammasome in DMD and explore a potentially promising treatment with MCC950 that selectively inhibits NLRP3. Methods Four‐week‐old mdx mice (n=6 per group) were orally treated for 2 months with MCC950(mdx‐T), a highly potent, specific, small-molecule inhibitor of NLRP3, and compared with untreated(mdx) and wild-type(WT) mice. In vivo functional tests were carried out to measure the global force and endurance of mice. Ex vivo biochemical and molecular analyses were performed to evaluate the pathophysiology of the skeletal muscle. Finally, in vitro tests were conducted on primary cultures of DMD human myotubes. Results After MCC950 treatment, mdx mice exhibited a significant reduction of inflammation, macrophage infiltration and oxidative stress (-20 to -65%, P<0.05 vs untreated mdx). Mdx‐T mice displayed considerably less myonecrosis (-54%, P<0.05 vs mdx) and fibrosis (-75%, P<0.01 vs mdx). Moreover, a more mature myofibre phenotype, characterized by larger-sized fibres and higher expression of mature myosin heavy chains 1 and 7 was observed. Mdx-T also exhibited enhanced force and resistance to fatigue (+20 to 60%, P<0.05 or less). These beneficial effects resulted from MCC950 inhibition of both active Caspase-1 (-46%, P=0.075) and cleaved gasdermin D (N-GSDMD) (-42% in medium-sized-fibres, P<0.001). Finally, the anti-inflammatory action and the anti-pyroptotic effect of MCC950 were also recapitulated in DMD human myotubes. Conclusion Specific inhibition of the NLRP3 inflammasome can significantly attenuate the dystrophic phenotype. A novel finding of this study is the overactivation of GSDMD, which is hampered by MCC950. This ultimately leads to less inflammation and pyroptosis and to a better muscle maturation and function. Targeting NLRP3 might lead to an effective therapeutic approach for a better management of DMD.